Towards Universal Equivalence in the Translations of Proverbs in Yoruba Literary Text - Olusanya Phillip Siji (Budapest International Research and Critics University, 2026)
The translation of proverbs presents a complex challenge when the source text’s cultural referents become obsolete or diverge from contemporary global norms. This study investigates the translational strategies employed to address culture-specific elements in Yoruba proverbs—particularly those touching on sensitive issues such as gender, security, and human rights—which risk being misconstrued as archaic or prejudicial in a globalised context. Adopting a hybrid theoretical framework of Cultural Universalism (CU) and Conceptual Metaphor Theory (CMT), the research analyses how translators negotiate the tension between cultural fidelity and universal intelligibility. The study examines proverb samples from French translations of Yoruba play, Rere run, written by Oladejo Okediji . The findings reveal that, often, Yoruba proverbs often rely on ancient ideologies that lack direct equivalents in the target culture’s cognitive framework. The study concludes that the synergistic application of CU and CMT enables translators to achieve Universal Equivalence: a strategy that preserves the pragmatic and didactic function of the proverb while modifying its cultural imagery to align with the sociopolitical and ethical standards of the target audience.